Study of the nuclear continuum using high resolution gamma and charged-particle spectroscopy (2012)
Abstract. We have used the 36Ar +28Si at 142 MeV fusion-evaporation nuclear reaction using the ArgonneTandem-Linac Accelerator System (ATLAS) accelerator facility in conjunction with Gammasphere and the Lund University andWashington University Silicon Array (LuWuSiA) for charged-particle spectroscopy at the Argonne National Laboratory. The high resolution and high granularity of the LuWuSiA array allow us to measure with very good accuracy the charged-particles energy and angular information. We use the experimental results and compare them to a simulation carried out with the code PaceTlm to extract information about the shape of the emitting nucleus at high excitation energy, E* ≈ 65MeV, and high angular momentum J ≈ 40ћ. The results of the simulation suggest that the ∞ particles are very sensitive to the nuclear deformation unlike protons and neutrons. At large compound nucleus deformation (ᵝ= 0:3), the -particles energy spectrum seems to develop an extra maximum suggesting fingerprints of the initial deformation. The setup LuWuSiA was fully simulated using Geant4 to help the data analysis and improve the interpretation of the experimental results.